The influence of intermittent venovenous hemodiafiltration on the course of acute kidney injury in multiple trauma victims - V.M. Dubyna; O.V. Kravets (Медицина неотложных состояний)
Background. Acute kidney injury (AKI) is a common complication of polytrauma that requires renal replacement therapy (RRT) in 10 to 28 % of cases. RRT methods can be divided into discrete, or intermittent, and continuous. There are currently no clear recommendations regarding the choice of the RRT method. The purpose was to study the effect of intermittent venovenous hemodiafiltration (HDF) on indicators of renal function, hemodynamics, homeostasis and inflammation in multiple trauma victims with rhabdomyolysis and AKI. Materials and methods. Fifty victims with multiple trauma complicated by rhabdomyolysis and AKI were examined. We investigated the levels of total creatine kinase and myoglobin, indicators of kidney function, frequency of vasopressor support, indicators of general blood analysis, liver complex, coagulogram, acid-base and gas composition of blood. The study was conducted upon admission, before the start and after the end of each HDF session and on the last day of treatment. Results. Multiple trauma with massive rhabdomyolysis led to AKI, manifested by oliguria and hyperazotemia (and from the 3rd day, by hyperkalemia), as well as cardiovascular failure, anemia, liver dysfunction, and inflammatory response. AKI progression to renal failure despite conservative therapy led to the beginning of HDF on 3.6 ± 0.8 days of hospital stay. HDF allowed to effectively reduce indicators of the renal complex and normalize the potassium level, and at the same time did not have a negative effect on hemostasis or other indicators of homeostasis. 72.9 % of victims needed two HDF sessions, 47.9 % — three, 31.3 % — four or more. The most pronounced reduction of hyperazotemia was observed after the second session. Among the survivors, restoration of adequate diuresis by the day 14 was observed in 39.3 % of cases. The mortality rate was 34.0 %. Laboratory markers of renal function were not significantly different between survivors and deceased; the difference was in markers of liver function, coagulogram and acid-base balance, as well as the need for vasopressor support. That is, the mortality was due to the progression not so much of kidney failure, but of the failure of other organs and systems. It should also be noted that the injury severity score among survivors was 23.5 ± 4.0 points, and among non-survivors — 40.5 ± 6.8 points (p < 0.001). Conclusions. Multiple trauma with massive rhabdomyolysis leads to the development of multiple organ failure. Intermittent HDF allows to quickly and effectively reduce azotemia and normalize potassium levels without adversely affecting coagulation or other indicators of homeostasis. Most multiple trauma victims need 2 or more sessions of HDF. Mortality remains high and primarily depends on the severity of anatomical injuries and the addition of other organs and systems failure.